Correlation among physical properties of parboiled milled rice during hydrothermal pretreatment processing - Muchlisyiyah, Jhauharotul; Shamsudin, Rosnah; Basha, Roseliza Kadir; Shukri, Radhiah; How, Syahmeer (Universiti Putra Malaysia, 2024)
The rice cultivar MR297 has a high harvesting yield but a low milling and head rice yield. Parboiling is one of the methods to increase the head yield of rice varieties. The colour of parboiled rice is intense due to husk colour absorption during soaking. This study researched the influence of hydrothermal pretreatment (soaking time and temperature) on the physical properties such as dimension, thousand kernel weight (TKW), density, volume expansion (Ve), colour, and hardness of parboiled milled rice. MR297 raw rice cultivars were soaked at 1:1 (w/w). Paddy was soaked at 50, 60, and 70°C for 1, 2, 3, 4, and 5 hr and steamed at 100°C for 20 min prior to drying for 24 hr at 38°C. It was discovered that the effects of soaking time and temperature varied with the physical properties of rice. Soaking time and temperatures were found to be significant (p<0.05) in terms of dimensional properties (length [L], width [W], and thickness [T]), TKW, density, Ve, colour (L*, a*, b*) and hardness of parboiled rice. The L, W, T, Ve, TKW, a*, and b* increase proportionally as time and temperature increased, while the density and L* were negatively correlated. The hardness was negatively correlated with the L and colour b* (yellowness) rice measurements. The principal component analysis (PCA) results revealed that the soaking time was associated with L, W, T, density, Ve, and colour properties based on the loading analysis in the PC1. In contrast, the temperature, TKW and hardness were associated with PC2.